2018
DOI: 10.1080/09540105.2018.1485632
|View full text |Cite
|
Sign up to set email alerts
|

Immune response induced by fermented milk with potential probiotic strains isolated from artisanal Cocido cheese

Abstract: Fifteen strains of lactic acid bacteria isolated from artisanal Cocido Mexican cheese were evaluated for their probiotic potential and capacity to modulate the immune system. The results revealed that the strains J20, J23, J24, J25, J27, J28, J32 and J37 presented the highest potential probiotic. Some strains showed resistance to antibiotics; however, they did not exhibit haemolytic activity or mucin degradation. The auto-aggregation capacity ranged from 9.54% to 47.80%, and the hydrophobicity was 21.1%, 63.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 64 publications
2
14
0
Order By: Relevance
“…Statistical differences ( p < 0.05) were not found between the milks. Bacterial cell concentrations established in fermented milks have shown immunomodulatory and anti-inflammatory effects in previous works [5,14,15,16,18,21], which suggests that bacterial populations found here may be effective on ameliorating induced inflammation.…”
Section: Resultssupporting
confidence: 60%
See 2 more Smart Citations
“…Statistical differences ( p < 0.05) were not found between the milks. Bacterial cell concentrations established in fermented milks have shown immunomodulatory and anti-inflammatory effects in previous works [5,14,15,16,18,21], which suggests that bacterial populations found here may be effective on ameliorating induced inflammation.…”
Section: Resultssupporting
confidence: 60%
“…Meanwhile, anti-inflammatory cytokines, such as IL-10 and IL-4, contribute to decreasing the inflammatory response in the intestinal mucosa [29]. In a previous study, the administration of fermented milk with J20 and J28 showed the capacity to regulate the cytokines IL-6 and IL-10 in serum samples after 21 days in a healthy murine model [18]. Although the mechanisms by which these bacteria activate the immune response have not been evaluated, other studies have suggested, for example, that the administration of Bifidobacterium breve in mice interacts with dendritic cells, bind to TLR2, a recognized polysaccharide structure of the cell wall, promote Trl cells, and induce Foxp3+ [30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tolerance to lysozyme, pepsin and Pancreatin: Tolerance to lysozyme, pepsin and Pancreatin was assessed following the method reported by Santiago et al (2018).…”
Section: Determination Of Probiotic Potentialmentioning
confidence: 99%
“…2018a; Santiago‐López et al . 2018b). Besides, it is widely known that these microorganisms could play an important role in imparting desirable sensory characteristics in the cheese.…”
Section: Introductionmentioning
confidence: 99%